Methodology for the mitigation of risks in the improvement of tertiary roads in Cundinamarca, Colombia - Sánchez Estrada, Juan Sebastián (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This paper is based on research conducted in risk management for road-type projects, especially, in the improvement of tertiary roads. It consists of the analysis of the risks applied to these types of projects, as well as the presentation of proposals for mitigation and reduction of the probability of impact and occurrence. Based on this, the risk identification and analysis proposed by the Project Management Institute (PMI) was carried out to develop a manual, which proposes a methodology and a step by step to carry out the proper construction of the rigid pavement reducing the risks latent to its occurrence and the work contingencies in the construction workplace. The manual for risk management in the improvement of tertiary roads was applied in a civil works project in the municipality of Soacha, Cundinamarca. This left positive results, where a high decrease in the impacts of risks established in principle was observed. This was reflected both in the decrease in risks and in the increase in the performance of civil works, as well as in the decrease in unforeseen costs, which makes the utility greater than initially was projected.